Modification of the Biorelevant Release Testing of Esophageal Applied Mucoadhesive Films and Development of Formulation Strategies to Increase the Mucosal Contact Time - Friederike Brokmann; Paul Simonek; Christoph Rosenbaum (MDPI AG, 2024)
The increasing prevalence of esophageal disease highlights the clinical relevance of novel, long-lasting mucoadhesive oral dosage forms. The EsoCap device enables targeted local application of films in the esophagus. Biorelevant test systems such as EsoPeriDiss are essential for early formulation development. To this end, the developed and already described release model for simulating the esophagus is being further developed for its potential for biorelevant mapping of the application site through complete tempering and investigation of biorelevant release media. Particularly viscous saliva formulations led to an extension of the retention time. In addition, possible formulation strategies for increasing the retention time of esophageal applied films are being evaluated, such as different film thicknesses, polymer grades and the influence of different active ingredient properties on the retention time. For highly soluble active ingredients, the film thickness represents an option for extending the retention time, while for less soluble substances, the choice of polymer grade may be of particular interest.